Plant Cytokinesis: Terminology for Structures and Processes. Issue 12 (December 2017) - Smertenko, Andrei; Assaad, Farhah; Baluška, František; Bezanilla, Magdalena; Buschmann, Henrik; Drakakaki, Georgia; Hauser, Marie-Theres; Janson, Marcel; Mineyuki, Yoshinobu; Moore, Ian; Müller, Sabine; Murata, Takashi; et al.
Abstract : Plant cytokinesis is orchestrated by a specialized structure, the phragmoplast. The phragmoplast first occurred in representatives of Charophyte algae and then became the main division apparatus in land plants. Major cellular activities, including cytoskeletal dynamics, vesicle trafficking, membrane assembly, and cell wall biosynthesis, cooperate in the phragmoplast under the guidance of a complex signaling network. Furthermore, the phragmoplast combines plant-specific features with the conserved cytokinetic processes of animals, fungi, and protists. As such, the phragmoplast represents a useful system for understanding both plant cell dynamics and the evolution of cytokinesis. We recognize that future research and knowledge transfer into other fields would benefit from standardized terminology. Here, we propose such a lexicon of terminology for specific structures and processes associated with plant cytokinesis. Trends: A large number of phragmoplast proteins have been identified. Electron microscopy/tomography studies have produced nanoscale information about the architecture of phragmoplast and cell plate assembly stages in cryofixed cells. Novel components of the cortical division zone and cell plate fusion site have been discovered. This information lays a foundation for understanding how plant cells memorize the division plane throughout mitosis and how the cell plate is guided to its predetermined attachment site. MAP65 and plus end-directed kinesins contribute to the maintenance of the antiparallel overlap of phragmoplast microtubules. In addition, the MAP65–TRAPPII interaction plays a key role in cell plate assembly. Actin filaments align parallel to microtubules in the phragmoplast, while some microfilaments extend from cell plate margin to guide its expansion towards the fusion site.